Managing school safety in Thailand: Assessing the implications and potential of a lean thinking framework - Pachernwaat Srichai (2018)
Child injuries are replacing infectious disease as the leading cause of mortality in developing countries. As school is one of the environments where children spend significant time during their formative years, school safety should be effectively managed, promoted, and prioritized. In Thailand however, school safety is considered to be of low priority compared with other educational issues, lacking effective policy, and with schools struggling to justify safety costs. This article proposes a novel application of lean thinking to control the cost, bureaucracy, and waste associated with managing and administering a safe school. Through a case study in northern Thailand, one primary school's current safety scenario is reviewed with regard to people, finance, and operations, before applying a lean framework to improve the handling of safety suggestions. Results show significant capacity to improve the management of school safety, along with management implications and potential to expand the framework beyond Thailand. © The Author(s) 2013.